Safety and preventive effects of rivaroxaban and low-molecular-weight heparin on deep vein thrombosis of lower extremity after total hip arthroplasty (Indian Journal of Experimental Biology (IJEB), 2022)
Deep vein thrombosis (DVT) is a common complication of skeletal surgery, which can cause disability and death in severe cases. Here, we have compared the preventive effects of rivaroxaban and low molecular weight heparin on DVT of lower extremity after total hip arthroplasty and the safety. A total of 310 patients who received total hip arthroplasty from May 2014 to June 2016 were divided into a rivaroxaban group (n=153) and a low molecular weight heparin group (n=157). The rivaroxaban group was orally administered with rivaroxaban (10 mg, qd) 12 h after surgery for 30 consecutive days, and the other group was subcutaneously injected with low molecular weight heparin calcium injection (0.6 mL, ad) for 7 consecutive days. The incidence rate of lower extremity DVT, drainage blood volume, hemoglobin decline, as well as preoperative and postoperative 7-d prothrombin time (PT), activated partial thromboplastin time (APTT), platelet (PLT) count and D-dimer level of the two groups were compared. The two groups had similar incidence rates of lower extremity DVT, drainage blood volumes and extents of hemoglobin decline (P >0.05). There were no significant differences in the preoperative and postoperative 7-d PT, APTT, PLT counts and D-dimer levels between the two groups (P >0.05). Rivaroxaban and low molecular weight heparin show comparable preventive effects on lower extremity DVT after total hip arthroplasty. Results suggest that rivaroxaban is superior than the low molecular weight heparin in terms of convenient use (oral administration), good compliance and absence of dose adjustment.